Seasonal and subtype differences in body mass index at admission in inpatients with anorexia nervosa. Issue 5 (10th February 2020) - Meule, Adrian; Schlegl, Sandra; Voderholzer, Ulrich
Abstract: Objective: In the general population, body weight is—on average—higher in the winter than in the summer. In patients with anorexia nervosa (AN), however, the opposite pattern has been reported. Yet, only a handful of studies exist to date that suffer from small sample sizes and inconsistent results. Therefore, the current study examined seasonal effects on body weight in a large sample of patients with AN to dissolve previous inconsistencies. Method: Clinical records of N = 606 inpatients (95.4% female) who received AN treatment at the Schoen Clinic Roseneck (Prien am Chiemsee, Germany) between 2014 and 2019 were analyzed. Results: Patients with restrictive type AN had lower body mass index at admission in the winter than in the summer. This difference was not found for patients with binge/purge type AN and patients with atypical AN. Discussion: Individuals with restrictive type AN show seasonal variations in body weight that are opposite to seasonal variations in body weight in individuals without AN. These seasonal effects are specific to the restrictive subtype and cannot be found for the binge/purge or atypical subtypes. Future studies that replicate this effect in other cultures or latitudes and that examine the mediating mechanisms are needed.